2015
DOI: 10.13102/sociobiology.v61i4.502-509
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive and Foraging Behavior of Two Stingless Bee Species in Greenhouse Mini Watermelon Pollination

Abstract: The growth of protected cultivation in world agriculture has led to crops traditionally cultivated in open field to be grown in protected environments, but this condition creates a physical barrier which prevents the access of natural pollinators to flowers (Guerra Sanz, 2008). Hand pollinating the flowers in a protected environment, as well as the application of hormones to induce fruit production, is laborious and increases production costs (Cruz & Campos, 2009). Thus, a more economical alternative would be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 29 publications
0
11
0
3
Order By: Relevance
“…bees have been widely used in various countries for greenhouse pollination (Velthuis & van Doorn, 2006), they are not globally distributed and are considered a difficult to control exotic pest in some regions where they have been introduced (Dafni et al, 2010). Stingless bees, Meliponini, have a more restricted distribution, and when they are introduced into a greenhouse environment, they need to adapt to foraging in a restricted area; also, they do not invariably visit the flowers that need pollination when under confinement (Bomfim et al, 2014). Given the current knowledge about honey bee management and the facility in finding beekeepers who have colonies available for pollination services practically throughout the world, honey bees have the potential to become an optimal solution for pollinating crops in greenhouses, if techniques can be improved to adapt these bees to foraging in closed environments (Katayama, 1987;Guerra-Sanz, 2008).…”
mentioning
confidence: 99%
“…bees have been widely used in various countries for greenhouse pollination (Velthuis & van Doorn, 2006), they are not globally distributed and are considered a difficult to control exotic pest in some regions where they have been introduced (Dafni et al, 2010). Stingless bees, Meliponini, have a more restricted distribution, and when they are introduced into a greenhouse environment, they need to adapt to foraging in a restricted area; also, they do not invariably visit the flowers that need pollination when under confinement (Bomfim et al, 2014). Given the current knowledge about honey bee management and the facility in finding beekeepers who have colonies available for pollination services practically throughout the world, honey bees have the potential to become an optimal solution for pollinating crops in greenhouses, if techniques can be improved to adapt these bees to foraging in closed environments (Katayama, 1987;Guerra-Sanz, 2008).…”
mentioning
confidence: 99%
“…Their smaller colony size and short flight range put them at advantage than the Apis species as pollinator of crops under enclosures. Several stingless bee species have been reported to provide adequate pollination services to many crops grown under protected cultivation, such as strawberry, eggplant, sweet pepper, tomato and cucumber [24], although their use for pollination purposes at commercial level is still in developmental stage [25]. The present results serve as a potential basis for integration of this species for managed crop pollination.…”
Section: Resultsmentioning
confidence: 76%
“…The top-working body position likely places pollen-carrying hairs on the bee's body in close proximity to stigmatic lobe surfaces. Bomfim et al (2015) observed that a greater area of the body contacted the reproductive parts of watermelon flowers when Scaptotrigona bees were top-working. In contrast, the duration of honey bee side-working did not vary consistently with nectar extraction, nor was it correlated with pollen deposition (Kuhn & Ambrose, 1984;Park et al, 2016).…”
Section: Discussionmentioning
confidence: 99%